2013
DOI: 10.1017/s1368980012005460
|View full text |Cite
|
Sign up to set email alerts
|

Consumption patterns of sweetened food and drink products in a Catholic Middle Eastern Canadian community

Abstract: Objective: The present study describes the consumption patterns of sweetened food and drink products in a Catholic Middle Eastern Canadian community and examines its associations with physical activity, sedentary behaviours and BMI. Design: A two-stage cross-sectional design was used. In Stage 1 (n 42), 24 h recalls enabled the identification of sweetened products. In Stage 2 (n 192), an FFQ was administered to measure the daily consumption of these products and to collect sociodemographic and behavioural data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
(82 reference statements)
2
4
1
Order By: Relevance
“…This study found an association between physical inactivity and daily soft drink consumption, and sedentary behavior with sweetened fruit juice consumption. These results are consistent with previous studies 15,19,32. While some previous studies13,15,19 found an association between substance use (smokers) and SSB consumption, this study found a positive association between problem drinking and soft drink consumption and in bivariate analysis a negative association between tobacco use and SSB consumption.…”
Section: Discussionsupporting
confidence: 93%
“…This study found an association between physical inactivity and daily soft drink consumption, and sedentary behavior with sweetened fruit juice consumption. These results are consistent with previous studies 15,19,32. While some previous studies13,15,19 found an association between substance use (smokers) and SSB consumption, this study found a positive association between problem drinking and soft drink consumption and in bivariate analysis a negative association between tobacco use and SSB consumption.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, consumption of processed products high in dietary sugars is recognised as an important contributor to the development of these diseases 6. As reported elsewhere, the consumption level of total sugars (all foods considered), ∼20% of diet, in this community is now similar to that consumed by the Canadian and Quebec population 7. The average daytime sleepiness score (8.2) and the prevalence of EDS (28%) measured in this report are within the range noted in Western countries 50.…”
Section: Discussionsupporting
confidence: 85%
“…In a previous report, we observed an inverse (but not a significant) relationship between consumption of sweetened products and BMI in the same community 7. These results, however, must be interpreted not only by taking into account that overweight and obese individuals may have under-reported their weight or under-reported their consumption of sweetened products, but also the cross-sectional design.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations